Oak stands productivity and rearing of Cinta Senese in central Tuscany - Fabbio G.; Grifoni F.; Gonnelli V.; Benvenuti C.; Franci O. (5. International Symposium on the Mediterranean Pig, 2007)
Renewed attention is nowadays being paid to the Cinta Senese, a local breed of pig native to the area of Siena (central Tuscany). Historically, its typical rearing environment included oak stands, the forest fruits being considered fundamental to characterize the quality of production. Given that the structure of the current forest types is very different from the stands managed in the past for this purpose, both acorn production and the period of fruit fall were monitored throughout four years in three sites around Siena. The most common oak forest types in the area, i.e., Quercus ilex, Quercus cerris and Quercus pubescens stands were considered. The period of fruit fall was September-March (holm oak); September-January (Turkey oak); whilst pubescent oak, which builds up the more degraded stands in the area, showed a very low and not significant acorn production. Finally, the sustainability of grazing under the forest cover is discussed.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)